Maya sanat galerisi - Savaş, Azime (My University, 2008)
MAYA SANAT GALERİSİ Türkiye’nin ilk uzun soluklu özel sanat galerisi olan Maya Sanat Galerisi, 1950-55 yılları arasında faaliyette bulunmuştur. Galeri,açık olduğu bu beş yıl süresince gerçekleştirdiği sergilerle,Türk kültür ve sanat dünyasında öncü bir rol oynamıştır. Adalet Cimcoz, Sabahattin Eyüboğlu ve Orhan Veli’nin bir araya geldikleri dost meclislerinde,ülkedeki büyük boşluğu görerek hayata geçirmeye karar verdikleri bir kültür sanat projesidir.Orhan Veli’nin açılışını göremeden vefat ettiği galeri, Sabahattin Eyüboğlu’nun büyük desteği ile Adalet Cimcoz tarafından Beyoğlu’nda açılmıştır. Adalet Cimcoz’un girişimi ile Galeri, ülkedeki büyük bir boşluğu doldurarak kısa sürede bir sanat merkezi haline gelmiştir. Dönemin önde gelen tüm sanatçıları, ressamları, gazetecileri vb. galeriyi her daim ziyaret etmişlerdir. Adalet Cimcoz’un renkli kişiliğiyle basında da her daim yer almıştır. Maya Sanat Galerisi’nin Türk kültür ve sanat dünyasına en büyük katkılarından birisi, sanatçılarla sanatseverler arasında köprü vazifesi görmesidir. Ayrıca, birçok genç sanatçı ilk sergilerini burada açarak sanat dünyasına merhaba demişlerdir. Galeri de sadece plastik sanatlar değil, karikatür, fotoğraf, edebiyat vb. diğer sanat dallarına da yer verilmiştir. Dönemin usta sanatçılarıyla genç sanatçıları bir arada sergi açma imkanı bulmuşlardır. Maya Sanat Galerisi, ülkemizde bir sanat piyasasının varolabilmesi için ve sanatçıların hak ettikleri değeri görebilmesi için büyük çaba sarf etmiştir. Galeride modern sanat desteklenerek ülke sanatının canlanması ve daha da ilerlemesi için katkıda bulunulmuştur. Türk kültür ve sanat dünyası, Maya Sanat Galerisi sayesinde sadece bir galeriye değil, her türlü sanat dalına kapılarını açan, sanatçıların ve sanatseverlerin bir araya geldikleri bir kültür merkezine kavuşmuşlardır. Adalet Cimcoz, beş yıl boyunca galeriyi ayakta tutabilmek için büyük bir mücadele vermiştir. Sanatseverlere sanat eser satın alma alışkanlığı kazandırmaya çalışılarak, yeri geldiğinde taksitli satış yöntemi gibi yollar bile denemiştir. Kurulduğu ilk günden itibaren, Türk kültür ve sanat dünyasına büyük katkıları olan, Maya Sanat Galerisi, düzenlediği kişisel ve karma sergilerle, özellikle genç sanatçılara verdiği destekle ve ülkede bir sanat piyasasının oluşması için verdiği mücadele ile yıllar sonra bile, unutulmamıştır.

MAYA ART GALLERY Maya Art Gallery which was the first long-life private art gallery of Turkey carried out its activities between 1950 and 1955. Maya played a Pioneer role in Turkish culture and art and made a substantial contribution to Turkish culture and life with the exhibitions that were held at the gallery during the aforementioned five years period. Maya Art Gallery wasa culture and art project that AdaletCimcoz, Sabahattin Eyüboğlu and Orhan Veli decided to bring to life perceiving the big gap in the country in the meetingswhere they cae together with a most friendly atmosphere. Unfortunately, Orhan Veli passed away without witnessing theinaugurationof the gallery; however the gallery was opened in Beyoğlu by Adalet Cimcoz with the great support of Sabahattin Eyüpoğlu. Through the iniatives of Adalet Cimcoz Maya Art Gallery had become the art center of the country within a very short period time filling a big gap in the country. Almost all of the leading artists, painters and journalists of that period always had paid a visit to the gallery. Maya Art Gallery had always held an important place in the press thanks to colorful personality of Adalet Cimcoz. The gallery served as a forum, as a bridge for interaction between the artist and art-lovers, and this had become one of it substantial contributions to Turkish culture and art life. Furthmore, the gallery provided opportunities for many young artists by allowing them to hold their first exhibitions and say hello to the world of art. The activities held in the gallery did not only consist of the plastic art but also other art disciplines such as caricature, photograph, literature and etc. The gallery provided opportunities for both notable famous played a very important role in the struggle of the existence of an art market in the country and in allowing the artist to receive the recognition of their worth that they deserve. The gallery supported modern art and made a great contribution to the art of the country by playing an important role in the development and improvement of the art and in bringing vitality to the art. Turkish culture and art had not only gained the opportunity of possessing a gallery but also a culturel center that opened its doors to any kind of art activities and where the artists of the period and art-lovers came together. Thoughout the aforementioned five year period Adalet Cimcoz always made a great effort for the survival of the gallery. It was always tried to allow art lovers to acquire a habit of art, and in accordance with this purpose several methods such as sales with installments were used. Maya Art Gallery which made substantial contributions to Turkish art and culture has taken its unforgettable place in Turk culture and art with numerous personal and mixed exhibitions that it had housed and in particular with its great support to young artists and with its very important role that it played in the struggle of the existence of an art market in the country.
Keywords: Galeriler, Sanat; Türk Sanatı